Influence of ZnF2 concentration on excitation energy transfer between Er3+ and Tm3+ ions in antimony-germanate glass ceramic - Golonko, Piotr; Kašík, Ivan; Mrázek, Jan; Żmojda, Jacek (Photonics Letters of Poland, 2024)
New broadband-emitting materials are still in demand for industrial, medical, and telecommunications solutions. Thus, new materials that improve the luminescence of lanthanide ions are in demand. Equally important seems to be the co-doping of the host material with different lanthanides, for example Er3+ and Tm3+. In co-doped materials, energy transfers between ions depend on lanthanide ions concentrations, host material chemical composition and structure. To improve the efficiency of energy transfer and radiative transitions, low-phonon matrices should be used. One of various solutions is the use of oxide-fluoride matrices, where the oxide part of the matrix provides the desired thermal and mechanical stability and the fluoride part provides a low-phonon environment for the ions. In this report, influence of concentration of ZnF2 on the co-doped oxide matrix was investigated in terms of luminescence changes. Full Text: PDF References J. Thomas, "Enhancing the optical performance of oxyfluoride glass ceramics by optimizing the oxide: Fluoride ratio and crystallinity for optical refrigeration", J. Non-Cryst. Solids 17, 100173 (2023), CrossRef X. Miao, „Crystallisation kinetics and structural stability of transparent CaF2 glass ceramics: Dependence of light transmittance on the amount of CaF2 added”, Ceram. Int. 46(10),15314 (2020). CrossRef K. Suresh, K.V. Krishnaiah, C. Basavapoornima, S.R. Depuru, C. K. Jayasankar, „Enhancement of 1.8 μm emission in Er3+/Tm3+ co-doped tellurite glasses: Role of energy transfer and dual wavelength pumping schemes”, J. Alloys Compd, 827, 154038 (2020). CrossRef X. Liao, X. Jiang, Q. Yang, L. Wang, D. Chen, „Spectral Properties of Er3+/Tm3+ Co-Doped ZBLAN Glasses and Fibers”, Materials, 10(5) (2017). CrossRef Z. Li, „The effect of melt-homogenization and heat-treatment on the optical properties of the rare earth doped oxyfluoride glass-ceramics”, J. Non-Cryst. Solids, 593, 121773 (2022). CrossRef Y. Zhu, „Concentration dependent structural, thermal and luminescence properties in Er3+/Tm3+ doped tellurite glasses”, J. Non-Cryst. Solids, 507, 19 (2019). CrossRef W. Ryba-Romanowski, J. Komar, R. Lisiecki, „Examining the Spectroscopic and Thermographic Qualities of Er3+-doped Oxyfluoride Germanotellurite Glasses”, Materials, 15(21) (2022). CrossRef Y. Tian i in., „The mid-infrared emission properties and energy transfer of Tm3+ /Er3+ co-doped tellurite glass pumped by 808/980nm laser diodes”, J. Luminescence, 214, 116586 (2019). CrossRef